A COMBINATION OF THE PROJECT BASED LEARNING MODEL AND VALUE CLARIFICATION TECHNIQUE IN IMPROVING STUDENTS' CRITICAL THINKING SKILLS - Rabiatul Adawiah; Dian Agus Ruchliyadi; Wardiani Halidi (Indonesian Journal of Educational Development (IJED), 2024)
Citizenship education learning is synonymous with learning that contains boring material because the learning model applied is monotonous and teacher-centred. This research aimed to analyse the effectiveness of the combination of the Project Based Learning (PjBL) and Value Clarification Technique (VCT) models in improving students' critical thinking skills. This study used a quantitative approach. The research population was junior high school students at SMP Negeri 21 Banjarmasin City. The research sample was 120 students from four groups selected random sampling technique, namely classes, that based on the homogeneity test, had relatively the same abilities. This research used a Quasi Experimental method with a Non-equivalent Control Group Research design. Data were analysed using the N-Gain test and Paired Sample Test (t-test) with the help of the SPSS 21.0 for Windows program. Based on the results of the analysis, it was known that (1) There were differences in students' critical thinking skills between the application of the Project Based Learning model and the application of the expository learning model; (2) There were differences in students' critical thinking skills between the application of the Value Clarification Technique model and the application of expository learning; (3) There were differences in students' critical thinking skills between the application of a combination of Project Based Learning and Value Clarification Technique and the application of expository learning. The highest N-Gain value for students' critical thinking skills was when applying a combination of Project Based Learning and Value Clarification Technique. Based on this, the combination of PjBL and VTC could be used as an innovative citizenship learning model solution to improve students' critical thinking abilities according to the demands of 21st century skills.